2018
DOI: 10.1371/journal.pntd.0006622
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic risk markers of leprosy in high-burden countries: A systematic review and meta-analysis

Abstract: Over 200,000 new cases of leprosy are detected each year, of which approximately 7% are associated with grade-2 disabilities (G2Ds). For achieving leprosy elimination, one of the main challenges will be targeting higher risk groups within endemic communities. Nevertheless, the socioeconomic risk markers of leprosy remain poorly understood. To address this gap we systematically reviewed MEDLINE/PubMed, Embase, LILACS and Web of Science for original articles investigating the social determinants of leprosy in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
103
3
28

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(139 citation statements)
references
References 46 publications
5
103
3
28
Order By: Relevance
“…A meta‐analysis conducted from 2006 to 2016 in countries with more than 1000 cases reported in at least five years of this period provided evidence for an association between unfavourable socioeconomic conditions and leprosy detection rates . In Brazil, the factors related to higher detection rates include a high percentage of children, a high average number of residents per municipality, poor water supply and lack of bathrooms .…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis conducted from 2006 to 2016 in countries with more than 1000 cases reported in at least five years of this period provided evidence for an association between unfavourable socioeconomic conditions and leprosy detection rates . In Brazil, the factors related to higher detection rates include a high percentage of children, a high average number of residents per municipality, poor water supply and lack of bathrooms .…”
Section: Discussionmentioning
confidence: 99%
“…Poverty has often been associated with an elevated risk of leprosy. 5 However, there is inadequate quantification of specific socioeconomic, demographic, and geographical variables that contribute to leprosy risk. Advancing our understanding of these risk factors can be applied to identify the communities in which surveillance and control efforts would be most effectively and efficiently focused.…”
mentioning
confidence: 99%
“…Association between house conditions and risk for leprosy development has been discussed in previous studies. According to Pescarini et al, 27 socio-economic status including house conditions strongly affects leprosy transmission. The results from another study conducted in a different population indicated that socio-economic conditions such as sanitation, house conditions, and economic status increase the risk of leprosy development.…”
Section: Discussionmentioning
confidence: 99%